(untitled) (International Journal of Engineering and Computer Science, 2015)
Recent advances in wireless sensor networks have prompted numerous new conventions particularly intended for sensor networks where energy awareness is a fundamental consideration. A wireless sensor network (WSN) consists of low cost, low power, small in size and multi functional sensor nodes. Routing protocols in WSNs emphasize on data dissemination, limited battery power and bandwidth constraints in order to facilitate efficient working of the network, thereby increasing the lifetime of the network. Routing protocols in WSNs are also application specific which has led to the development of a variety of protocols. WSN has a design trade-off between energy and communication overhead which forms the nerve center of the routing techniques. In this paper we present a survey of state-of-the-art routing techniques in WSN.